Beyond Hydrofunctionalisation: A Well‐Defined Calcium Compound Catalysed Mild and Efficient Carbonyl Cyanosilylation. Issue 6 (15th January 2018) - Yadav, Sandeep; Dixit, Ruchi; Vanka, Kumar; Sen, Sakya S.
Abstract: Organocalcium compounds have been reported as efficient catalysts for various transformations, for cases in which one of the substrates contained an E−H (E=B, N, Si, P) bond. Here, we look at the possibility of employing an organocalcium compound for a transformation in which none of the precursors has a polar E−H bond. This study demonstrates the utilization of a well‐defined amidinatocalcium iodide, [PhC(N i Pr)2 CaI] (1 ) for cyanosilylation of a variety of aldehydes and ketones with Me3 SiCN under ambient conditions without the need of any co‐catalyst. The reaction mechanism involves a weak adduct formation between1 and Me3 SiCN leading to the activation of the Si−C bond, which subsequently undergoes σ‐bond metathesis with a C=O moiety. Such a mechanistic pathway is unprecedented in alkaline earth metal chemistry. Experimental and computational studies support the mechanism. Abstract : Exact calcium : This work describes the first use of a well‐defined calcium compound for cyanosilylation of a range of aldehydes and ketones. Spectroscopic and DFT studies propose an unprecedented mechanism that involves a weak adduct formation between the catalyst and Me3 SiCN, followed by σ‐bond metathesis with the C=O group.